CREATIVITY IN THE CREATIVE WRITING OF INDONESIAN JEDDAH SCHOOL STUDENTS - Kartika, Ajeng Dianing; Arista, Cicik; Mintarsih, Mintarsih; Sutikno, Sutikno (Universitas Negeri Surabaya, 2024)
This research aims to describe creativity in the creative writing of Jeddah Indonesian School students. Creativity is one aspect that determines the excellence of a piece of writing. Creativity is the ability to produce something new. Creativity needs to be present in writing because the more creative it is, the better the writing. This research is qualitative research using descriptive methods to describe creativity in the creative writing of Jeddah Indonesian School students. The results of this research reveal that the stories and poetry written by the Jeddah Indonesian School students are creative writing. In the story written by the Jeddah Indonesian School students, there are elements of creativity in it, namely 1) theme creativity; 2) characters and characterization; 3) background; 4) groove; 5) mandate; and 6) language style. Then, there are also elements of creativity in poetry written by students at the Jeddah Indonesian School. The elements of creativity are 1) theme creativity; 2) title; 3) language style; and 4) instilling values.